Tepung Rumput Laut (Eucheuma Cottonii) Menaikkan Level Superoksida Dismutase (Sod) Ginjal Tikus Hiperkolesterolemia - Wresdiyati, Tutik; Budi Hartanta, Ans; Astawan, Made (Jurnal Veteriner, 2012)
Hypercholesterolemia condition was reported can decrease activities of antioxidant superoxidedismutase, catalase, and glutathione peroxide. This study was conducted to observe the role of seaweed(Eucheuma cottonii) powder in increasing the level of antioxidant cooper, zinc-superoxide dismutase (Cu,Zn-SOD) in kidney tissues of hypercholesterolemic rats. Twenty male Wistar rats were used in this study.Those rats were divided into four groups ; (1) Negative control group (A), (2) and (3) werehypercholesterolemic groups that were treated with 5% (B), and 10% (C) of seaweed powder, and (4)Hypercholesterolemic group as positive control (D). The treatment was carried out for 35 days.Hypercholesterolemia condition (>130 mg/dl), except for group A, was achieved by feeding the rat withcommercial diet containing 1% cholesterol and drinking water ad libitum for 40 days. Serum total cholesterolwas analyzed both before and after treatment. Rat kidneys were taken at the end of treatment, andprocessed by using paraffin embedding standard method. The tissues were then stained usingimmunohistochemical technique to Cu,Zn-SOD. The results showed the seaweed powder decreased serumtotal cholesterol, increased caecum cholesterol, repaired alteration of kidney tissues, and increased thelevel of antioxidant Cu,Zn-SOD in the kidney of hypercholesterolemic rats. Dietary fibers and antioxidantactivity of 10% seaweed powder was better than the of 5%.
Keywords: Superoxide dismutase (SOD), seaweed-Eucheuma cottonii, kidney, hypercholesterolemia, immunohistochemistry